In-Vitro Total Tocopherols, Phenol and Anti-oxidative Levels of Seeds’ oil of Telfairia occidentalis - Aguebor-Ogie, N.B.; Odigie, M.O.; Nwajei, O.E.; Eriyamremu, E.G. (International Journal of Scientific Research in Biological Sciences, 2022)
The seeds of fluted pumpkins are usually eaten boiled or pulverized and taken as food additive locally. As a result of this manner of utilization by the locals, this study was conducted to ascertain the contents of the total tocopherol, phenolic and the antioxidative property present in the oil of the seed. The pods of the fluted pumpkin were gotten from a farm within the Benin metropolis, Nigeria. The seeds were ground in a blender and afterward exposed to soxhlet extraction. Other standard methods were employed in this study. The quantitative analysis of these parameters showed Total Tocopherols (76.0 mg/kg ± 3.11), Total phenolic (3.34 mg of garlic acid equivalent ± 0.15). Percentage inhibition of DPPH was recorded to be 47.95 % ± 3.47, Nitric oxide scavenging capacity was 56.47 % ± 2.37 and ABTS was 51.06 % ± 2.60 respectively. The findings revealed that the seed oil of T. occidentalis possessed beneficial antioxidant properties which could be harnessed in management of disease like diabetes and cancer among others.